FREQUENCY OF PRIMIGRAVIDA IN PATIENTS WITH ECLAMPSIA - Faiza; Ruqqia Sultana; Jawaris Batool; Shah Khalid; Abdul Majid Khan (Journal of Ayub Medical College Abbottabad, 2023)
Background: Pregnancy-induced hypertension (PIH) occurs in about 5% of pregnancies and is a major cause of high perinatal and maternal morbidity and mortality. In several international studies, primigravidas were associated with a significantly higher incidence of eclampsia. The local studies so far have a small sample size and mainly focus on preeclampsia in all pregnant women. limited data is available on the frequency of eclampsia in primigravidas in our population. This study aims to determine the frequency of primigravidas in patients with eclampsia after 20 weeks of gestation. Methods: This descriptive Cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Ayub Teaching Hospital Abbottabad from 7/10/2020 to 7/4/2021. A total of 134 patients were observed. Diagnosis of eclampsia was based upon obstetrical history, presence of fits or coma, raised blood pressure and presence of proteinuria on urine complete examination. Immediate management included stabilizing the patient and delivery by Induction of labour or Caesarean section. The guardians of the patients explained the purpose and the benefits of the study and informed written consent was taken. Results: Our study shows that among 134 patients, 96(72%) patients were in the age range of 18-27 years while 38 (28%) patients were in the age range of 28-35 years. The mean age was 30 years with SD±10.94. Eighty-two (61%) patients had a POG range ‰¤34 weeks while 52 (39%) patients had a POG range >34 weeks. Forty-eight (36%) patients had BMI <27 Kg/m2 while 86 (64%) patients had BMI >27 Kg/m2. Fifty-six (42%) patients had a positive history of hypertension while 78(58%) patients had a negative history of hypertension. Out of 134 patients 102(76%) were primigravidas while 32(24%) were multigravidas. Conclusion: Our study concludes that the frequency of primigravidas was 76% in patients with eclampsia after 20 weeks of gestation presenting at tertiary care hospital Abbottabad.